Sensores baseados em nanofios semicondutores de SnO2: fotodetector de luz UV e sensor de gás - Araujo, Estacio Paiva (Universidade Federal de São Carlos, 2022)
In this work, sensors employing SnO2 semiconductor nanowires as active layer for gas and light detection were built. SnO2 nanowire samples were grown by VLS (VapourLiquid-Solid) method and morphological and structural properties were analyzed. XRD results exhibited SnO2 tetragonal rutile phase, within space group P42/mnm and lattice parameteres of a = b = 4.73 Å and c = 3.18 Å (JCPDS 41-1445). SEM images confirmed the desired morphology and TEM images revealed monocristaline character. Two different sensors’ architecture were chosen: a Metal-Semiconductor-Metal (MSM) with a nanowire network and a Field Effect Transistor with a single nanowire (NWFET). Current-voltage measurements of the SnO2 nanowire network devices with and without ultraviolet (UV) and visible (VIS) irradiation ranges were studied. Results indicated that a barrier is formed between the nanowire network and metallic contact when in absence of light, whereas under UV illumination there was an appreciable photoconductive gain and a small one under VIS illumination. NWFET’s values of charge density and mobility were estimate, of 1.6x1019 cm-3 and 3.7x10-4 cm2/Vs, respectively. Under UV illumination, the NWFET presented an ambipolar behavior, while under VIS illumination a unipolar response. SnO2 nanowire network’s photoresponse had a ION/IOFF ratio of 170 and 8.2 for UV and VIS light, respectively. In addition, response time was 2.8 s for UV light and 98s for VIS light, althought UV light measurements presented multiple decay times of 0.55 s and 145.84 s and for VIS light only one decay time of 153 s. NWFET photodetector response curves displayed a ION/IOFF ratio of 309 and 57 for VDS = + 1 V and VDS = - 1 V, respectively. For a positive voltage, VDS = + 1 V, the rise time was about 0.59 s and decay time was 0.63 s. Under a negative applied voltage, VDS = - 1 V, rise and decay times were 0.68 s and 0.75 s, respectively, were obtained. For the VIS light condition, no photocurrent variation in the NWFET was observed. The SnO2 nanowire network device was also used to study gas sensoring at room temperature. Sensor response, (), was found to be about 32 % and 9 % for acetone concentrations of 970 ppm and 50 ppm, respectively. In order to optimize and enhance the reponse, differentvii values of applied voltage were tested, resulting in a response of 32 % for V = + 9 V and 49 % for V = + 0.1 V. Given that, smaller values of applied voltage improved our sensor’s response.
Sensors based on SnO2 semicondutors nanowires: UV photodetector and gas sensor
Keywords: Nanofios; Oxido de estanho; Sensores; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA::ESTRUTURAS ELETRONICAS E PROPRIEDADES ELETRICAS DE SUPERFICIES INTERFACES E PELICULAS